From Wetlands to Worries: A Study of the Constructed Wetlands Model in Antibiotic Resistance Alteration - Ridwan Muhamad Rifai (International Journal of Integrated Engineering, 2025)
Antibiotic resistance in wastewater is an emerging health concern, as resistant coliform bacteria complicate treatment processes and pose significant risks to public health. Constructed wetlands (CWs) offer a promising and sustainable solution for wastewater treatment, although their effectiveness in reducing coliforms and mitigating antibiotic resistance varies. This study aimed to evaluate the effectiveness of a single CW system employing Typha sp. as the phytoremediation agent planted in Lightweight Expanded Clay Aggregate (LECA) on antibiotic resistance alteration. Samples were collected from both the inlet and outlet of the system after a 48-hour treatment. Total coliform enumeration and single colony isolation were performed to assess the abundance of coliform bacteria and antibiotic resistance. The minimum inhibitory concentration (MIC) of penicillin-G was tested using the diffusion disk method. Results showed a significant reduction in total coliform abundance (0.52 log reduction, 69.53%, p-val = 0.001). However, antibiotic resistance was increased, with both inlet and outlet samples exhibiting a MIC of 800µg/ml and diameter inhibition zones of 7.8±1.8 mm and 2.7±0.9 mm at 33 units of Penicillin-G, respectively. These findings suggest that CWs may promote antibiotic resistance in certain circumstances, potentially due to treatment efficiency, microbial dynamics, and horizontal gene transfer following selective pressures.